2018
DOI: 10.1007/s12350-017-0826-y
|View full text |Cite
|
Sign up to set email alerts
|

PET/CTA detection of muscle inflammation related to cholesterol crystal emboli without arterial obstruction

Abstract: Cholesterol crystal emboli triggered muscle inflammation and necrosis with an intact circulation. PET/CTA may help in the early detection of inflammation caused by CCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…In a previous study on aspirates from coronary arteries of patients during catheterization for myocardial infarction we had demonstrated that macrophages were attached to CCs and appeared to be binding and degrading them similar to what we found with bacteria in this study [11]. Also, similar findings were noted during CCs emboli in muscle [14]. Other reports have shown that S. aureus and Mycobacterium tuberculosis have the capacity to internalize and metabolize cholesterol thus utilizing free and esterified cholesterol as a potential source of nutrition and/or incorporation into the cell membrane as reported for mammalian cells [20,21].…”
Section: Plos Onesupporting
confidence: 89%
See 1 more Smart Citation
“…In a previous study on aspirates from coronary arteries of patients during catheterization for myocardial infarction we had demonstrated that macrophages were attached to CCs and appeared to be binding and degrading them similar to what we found with bacteria in this study [11]. Also, similar findings were noted during CCs emboli in muscle [14]. Other reports have shown that S. aureus and Mycobacterium tuberculosis have the capacity to internalize and metabolize cholesterol thus utilizing free and esterified cholesterol as a potential source of nutrition and/or incorporation into the cell membrane as reported for mammalian cells [20,21].…”
Section: Plos Onesupporting
confidence: 89%
“…Initial studies were conducted in vitro to evaluate the growth and adhesion characteristics of clinical strains of Staphylococcus aureus (ATTC #43300) and Pseudomonas aeruginosa (ATTC #27857) to CCs. Crystals were synthesized by dissolving cholesterol powder in methanol followed by evaporation as previously described [14]. To validate S. aureus and P. aeruginosa adherence to CC was specific and not related to the shape or hardness, we used plastic microspheres (250 μm) and ground glass shards as controls glued to coverslips.…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…Xie et al [27] showed that mice with muscle injury induced by electroporation show increased uptake of 64 Cu, thus demonstrating 64 Cu-Cl 2 PET/CT as a new molecular imaging technique for skeletal muscle. Recently, Pervaiz et al [28] showed that 18 F-FDG PET/CT can be used for imaging inflammation and muscle injury caused by cholesterol crystal emboli. However, these studies focused on the use of radiopharmaceuticals to assess a specific physiological disorder that cannot explain the whole SM recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Also, NETs partially contribute to this process (C. Shi, T. Kim, S. Steiger, S. R. Mulay, B. M. Klinkhammer, T. Bäuerle, M. E. Melica, P. Romagnani, L. Yang, D. Möckel, M. Baues, E. Mammadova‐Bach, B. Sanne, J. W. M. Heemskerk, A. Braun, T. Lammers, P. Boor, H. J. Anders, unpublished observation). In contrast, small amounts of CCs that do not cause endothelial cell injury remain inside the vasculature without triggering crystal clots .…”
Section: How Do Crystals Trigger Thrombosis?mentioning
confidence: 98%
“…The clinical presentation of the cholesterol embolism syndrome is dominated by ischemic tissue injury, and histopathological examination demonstrates how CCs impact the vascular wall [83]. However, not the crystals In contrast, small amounts of CCs that do not cause endothelial cell injury remain inside the vasculature without triggering crystal clots [86].…”
Section: How Do Crystals Trigger Thrombosis?mentioning
confidence: 99%